Spatial distribution of arsenic in groundwater of southern Nepal - Yadav I.C.; Singh S.; Devi N.L.; Mohan D.; Pahari M.; Tater P.S.; Shakya B.M. (My University, 2025)
Groundwater is a significant source of drinking water in virtually all parts of the world. Protected groundwater is safer to drink, in terms of microbiological quality, than is water from open dug wells and ponds (World Bank 2005). However, groundwater is notoriously prone to chemical and other types of contamination, such as arsenic (As) that derives from natural or anthropogenic sources. © 2012 Springer Science+Business Media, LLC.